Fifth annual report - Mew, E. B. ; Miller, Mary F. ; Norman, E. M. ; Roberts, D. ; Galbraith, H. ; Worden, M. ; Daukes, A. ; Waterworth, E. M. ; Mottram, D. B.; Capener, Norman (1932)
1932 1932 1930s 86 pages : illustrations [photograph] Photo by the "Western Morning News Co., Ltd." THE ANGELA CONVALESCENT HOME, TIPTON ST. JOHN. (Convalescent Annex to the Princess Elizabeth Hospital.) 292/841.51/2/2